The Guardian of the Integral Vision of Islamic Practice: The Naqshabandi Sufi Order in Indonesia - Umam, Saiful (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
This article, particularly the discussion on pesantrens, shows that only tariqa which supports fiqh is acceptable to and practiced by kiai and santri. This contradicts Trimingham's argument that Indonesians prefer heterodox mysticism. Comparing Muslims in Africa and Indonesia, Trimingham argues that Muslims in Indonesia place more emphasis on